Peranan Gizi dalam Pencegahan Penyakit - Fadjar Ramadhan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to explore the role of nutrition in disease prevention and identify the factors influencing the nutritional status of the population in Indonesia. Using a qualitative descriptive approach, this research analyzes scientific literature and secondary data from official sources such as the Central Statistics Agency (BPS) and the Indonesian Ministry of Health. The analysis results indicate that macro and micronutrients, such as complex carbohydrates, plant-based proteins, healthy fats, and vitamins and minerals, play a significant role in reducing the risk of chronic diseases such as type 2 diabetes, heart disease, and cancer. The Mediterranean diet and plant-based eating patterns have proven effective in improving health and preventing disease. However, Indonesia faces complex nutritional challenges, including a high prevalence of stunting in children and rising obesity rates in adults. Stunting is primarily caused by limited access to nutritious food and lack of nutritional knowledge, while obesity is associated with high-calorie diets and low physical activity. This study suggests increasing nutrition education, access to nutritious food, and promoting healthy lifestyles as essential steps to address nutritional problems in Indonesia and improve the overall quality of life.